Síndrome de burnout e violência simbólica entre profissionais de saúde no contexto Covid-19 - Araújo, Ana Lúcia Belarmino de (2022)
Introduction: The world scenario related to the pandemic to the new coronavirus has brought changes in the work process of health professionals with repercussions on their physical and mental health. Objective: To analyze the levels of Burnout Syndrome and reveal Symbolic Violence from the levels of Burnout Syndrome among health professionals in the context of COVID-19. Method: The study was developed in two stages. In the first stage, an integrative review was carried out on the evidence on Burnout Syndrome among health professionals in the face of COVID-19. In the second stage, an empirical study of the mixed convergent parallel type was developed, carried out through interviews in the virtual environment with health professionals. A sociodemographic instrument and the Cuestionario para la Evaluación del Syndrome de Quemarse por el Trabajo - CESQT and a semi-structured interview script were used. Results: The integrative review showed the occurrence of Burnout Syndrome among health professionals in coping with COVID-19, evidenced by work exhaustion, high levels of stress, scarcity of supplies, inappropriate working conditions and lack of institutional support in decision-making. For the empirical study, the sample consisted of 40 participants, of which 36 (90%) were COVID-19 reference professionals, 32 (80%) were female, 19 (47.5%) were married, between 36 and 47 years of age. age 22 (55%), workload 20 to 40 hours 25 (62.5%). Quantitative data were analyzed using the Statistical Package for the Social Sciences for Windows (SPSS) software, version 20 (IBM-SPSS, 2016). The analysis of the direct scores of the dimensions of the Cuestionario para la Evaluación del Syndrome de Quemarse por el Trabajo - CESQT were carried out with the aid of Excel software, which classified the participants in Profile 1-24 (60%) moderate level of SB, not disabling by the work and Profile 2- 08 (20%) high level of BS, disabling for work, totaling 80% of the participants of this study presenting BS. The textual corpus from the interviews was analyzed with the help of the IRAMUTEQ software, with a rate of 91.61%, considered in the Descending Hierarchical Classification (CHD). The dendrogram shows the corpus delimited in three lexical classes. The first partition formed class 2 (Mental Suffering) and class 1 (Institutional Violence) that communicate and the second partition formed class 3 (Subjectivity and Symbolic Violence). Conclusion: The integrative review showed that Burnout Syndrome is a reality among health professionals, knowing this reality can support managers to implement protection, prevention and health promotion actions in the work environment. Empirical research showed that most participants had moderate and high levels of Burnout Syndrome, revealing the Symbolic Violence reproduced in the speeches of health professionals, enabling the integration of quantitative and qualitative results and expanding the understanding of these two phenomena in the work process of these health professionals.